Decreased Ang-(1-7) and Downregulated Intrarenal RAS May Contribute to the Direct Podocyte Injury With Proteinuria in Preeclampsia. (August 2019) - Chen, Guixiang; Jin, Xiaohong; Zhang, Lihong; Niu, Jianying; Gu, Yong
The mechanisms of proteinuria development in preeclampsia (PE) are still enigmatic. Renin–angiotensin system (RAS) components may play a role. Maternal serum and urinary concentrations of angiotensin-(1-7) [Ang-(1-7)], angiotensin II (Ang II), and angiotensinogen in women with PE (n = 14), gestational hypertension (n = 14), and normal pregnancy were quantified. The alteration in these concentrations was used to evaluate their relationships with podocyturia and proteinuria in PE. In addition, the podocytes cultured in vitro were interfered in serum of preeclamptic and normotensive pregnant women, with or without Ang-(1-7). The morphologic change in podocyte was observed using a microscope. The changes in podocyte-specific proteins (nephrin, CD2-associated protein [CD2AP]), the cytoskeletal protein F-actin, the tight junction protein (ZO-1), and Mas receptor (MasR) were examined by immunofluorescence. Western blot was used to examine the expression and variation of MasR. We found that the concentrations of RAS components were associated with prepartal urinary podocyte number, random urine albumin/creatinine ratio, blood pressure, and renal function. The expression of nephrin, F-actin, ZO-1, and MasR on podocytes interfered in serum of PE was significantly decreased compared to normal control and normal pregnant serum group in vitro, yet their expression was significantly increased after coculture by 10 −6 mol/L Ang-(1-7) and the preeclamptic serum. The expression of CD2AP had no significant difference. We concluded that decreased Ang-(1-7) and downregulated intrarenal RAS contributed to the direct podocyte injury with proteinuria in PE.